Developer Relations (DevRel) Roles: an Exploratory Study on Practitioners’ opinions - Oliveira, Raphael; Ajala, Camila; Viana, Davi; Cafeo, Bruno; Fontão, Awdren (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2021)
Amazon, Google, and Facebook are examples of organizations that are investing in Developer Relations (DevRel) teams to support the synergy among developer communities’ expectations and the organization’s goals. The DevRel strategies (e.g., engaging and maturing developer communities) require the understanding of team structure to improve results. Identifying roles is a critical activity because DevRel people must plan, perform and monitor specific strategies to attract, engage, and mature developer communities. This research investigates the DevRel Roles by describing definitions and skills for each role. We synthesize the ”voice” of 116 practitioners from 19 countries with a grey literature review. We discuss nine identified roles regarding definition and skills. The roles include, for example, Developer Programs Engineer, Developer/Technical Advocate, Developer/Technical Evangelist, and Technical Writer. We noticed a lack of standardization of roles in DevRel.